2020
DOI: 10.3390/nu12123848
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Prevalence of Fruit and Vegetable Consumption in Spanish Workers

Abstract: The present study aims to examine the differences in daily fruit and vegetable consumption in the working population in Spain. A cross-sectional study was conducted, using data from the 2017 National Health Survey (n = 10,700 workers aged between 18 and 65 years). The daily consumption of fruit and vegetables was evaluated using two items included in a food frequency questionnaire. Occupations were classified into the 17 main groups of the National Classification of Occupations of 2011 (CNO-11). The prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…In fact, having a better knowledge of an adequate vegetable intake has been related to higher vegetable consumption [22], and a higher educational level has been related to better nutritional knowledge [43]. In Spanish workers aged between 18 and 65 years old, health care professionals, scientists, engineers, and teachers had the highest vegetable consumption [17]. Thus, the association between a higher educational level attained and the alignment with vegetable intake recommendations may serve as an indicator of social inequality in health [47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, having a better knowledge of an adequate vegetable intake has been related to higher vegetable consumption [22], and a higher educational level has been related to better nutritional knowledge [43]. In Spanish workers aged between 18 and 65 years old, health care professionals, scientists, engineers, and teachers had the highest vegetable consumption [17]. Thus, the association between a higher educational level attained and the alignment with vegetable intake recommendations may serve as an indicator of social inequality in health [47].…”
Section: Discussionmentioning
confidence: 99%
“…Though some studies have analyzed the social and demographic determinants of vegetable consumption, it appears that the relation between vegetable consumption and sociodemographic factors is not obvious. Being a woman [16,17] and a more educated individual [18,19] have been related, with some consistency, to more vegetable consumption. However, older adults have been identified as larger consumers of vegetables in some studies [20,21] but as lesser consumers in others [22], and being married has shown associations to a better intake of vegetables [23] or to a poorer one [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fast food advertisements on social media could also hinder the ability of young adults to opt for healthy eating behaviors [ 44 ]. Workers in rotating shifts, temporary contacts, and manual labor consume fewer fruits and vegetables, which is associated with longer working days, lower educational attainment, and higher levels of stress [ 45 ]. Since around 18.9% of the Peruvian GDP is produced by the informal sector (composed of >70% of the economically active population) [ 46 ], a large sector of the working force is at increased risk of AO.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence could be explained by a variety of factors, such as: (a) the type and duration of nutritional treatment received [ 37 , 38 ], highlighting the importance of follow-up to assess the efficacy of the intervention in the short and long term [ 39 , 40 ]; (b) motivation: as one of the facilitating factors in adherence to FV consumption [ 41 , 42 ], versus who was assigned to the control group; (c) access to information: adherence may be hampered due to the fact that practical aspects of the assigned intervention are unknown, such as portion sizes and the need for food variability [ 43 ]; (d) employment status and occupation: occupation gathers information on life styles and conditions related to education and income level; at a general level, a better professional qualification provides better working conditions and higher income, conditions associated with a higher prevalence of FV consumption [ 44 , 45 ]; (e) psychosocial stress: subjects with a history of cardiovascular disease undergoing a nutritional intervention [ 46 ], such as the consumption of FV according to recommendations assigned by the professional, in the long term generate allostatic load, that is, a maladaptive response, in this case not following the recommendations indicated [ 47 ]; (g) compensatory health beliefs: a factor that can influence adherence to FV consumption and consists of the belief that unhealthy behavior can be compensated; for example, eating unhealthily can be offset by exercising [ 42 ]; or, finally, (h) psychotherapeutic interventions: among psychotherapeutic interventions for modifying behaviors to promote adherence to nutritional interventions [ 48 ], we find Behavioral Activation (BA), focused on the reduction in avoidance behaviors and the development of routines and rewarding behaviors that allow greater adherence to FV consumption in adults with subsyndromal symptoms of depression [ 49 ].…”
Section: Discussionmentioning
confidence: 99%